Radiographic and ultrasonographic assessment of liver size in dogs with hepatic affections - Singh, Baltej; Mohindroo, J.; Sangwan, V.; Gupta, Kuldip; Singh, Opinder (Indian Journal of Veterinary Surgery, 2026)
The study was conducted on 25 dogs suffering from hepatic affections i.e., hepatitis (n=17) and liver neoplasms (n=8) and included common breeds of dogs. The objective of the study was to establish radiographic and ultrasonographic morphometry of various liver lobes in dogs with hepatitis and liver neoplasms. The animals were evaluated on the basis of signalment, history, clinical signs, haematology, biochemistry, radiographic and ultrasonographic findings. Radiographic linear measurement of liver in lateral recumbency ranged from 8.23 cm to 20.02 cm for animals with hepatitis, and 9.02 cm to 19.10 cm for animals with suspected liver neoplasms. Evaluation of liver size by radiography was not a reliable method due to wide variations in the breed size. On the basis of ultrasonography mean size of liver lobe was 4.58±0.28 cm (range 3.98-12.98 cm) on the basis of 95% confidence interval irrespective of liver lobe for animals with hepatitis. The size of liver for animals suspected with liver neoplasm was 3.33±0.38 cm with 95% confidence interval (range 2.42-14.01 cm) irrespective of liver lobe. Reduced appetite, pale mucus membrane, fever, vomiting, anaemia, elevated liver function test enzymes such as AST, ALT, ALKP, GGT were hallmarks of hepatic affections like hepatitis and liver neoplasm in dogs. The correlation of history, clinical signs, haematology, biochemistry and ultrasonography findings aided in the diagnosis of hepatic affections in dogs.